Analysis Of Strategies Used To Translate Idiomatic Sentences From Indonesian To English Found In Folklore’s Book Of Malin Kundang - Eva Febriana Citranita Gulo; Ervina Br Tarigan; Dewi Purnamasari Laia Laia; Sondang Manik; Lastri wahyuni Manurung (Universitas Pahlawan Tuanku Tambusai, 2023)
This descriptive qualitative study mainly describes the translation idiomatic sentence found in Folklore’s book of Malin Kundang. However, the process of translating is not as simple as switching the meaning of word for word based on the literal context. Idioms are one of the most problematical components of language. Idioms cannot be easily to translate because their meaning is unpredictable. This study is aimed (1) finding out the idiom expressions in Folklore’s book of Malin Kundang, (2) finding out the meaning of the idiom expressions in Folklore’s book of Malin Kundang, and (3) the kinds of strategies which are used in translating the idiomatic expression in Folklore’s book of Malin Kundang. The data were collected by reading the Folklore’s book of Malin Kundang in Indonesian version and listing all the idioms found in the source text and their translation in the target text, displaying each of them into tables.